JURIDICAL REVIEW OF BANKRUPTCY CONDITIONS AND DELAY OF DEBT REPAYMENT OBLIGATIONS - Hidayat, Anwar; Abas, Muhamad; Purwana, Dalih (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Bankruptcy results in a general confiscation of all assets of the bankrupt debtor (budel bankrulit). An important phase in the bankruptcy process is the insolvency stage. Based on the explanation of Article 57 paragraph 1 of the Bankruptcy Law and PKPU, what is meant by insolvency is the state of inability to pay, this is in line with the Central Jakarta Commercial Court Decision Number: 44 / PDT. SUS. PAILIT/20 20/PN. TRADE. JKT. PST. That PT. Pazia Retailindo was declared bankrupt. Application for bankruptcy filed by PT. Dana Kaya through its Directors, namely Sri Dewi Endang Mumpuni and Ambar Bawono on October 20, 2020, was represented by the appointed legal representative, namely PARLIN SIHOMBING, S.E., S.IP., S.H. Advocate at the Law Firm BELASSANDRO TORUAN &; PARTNERS. The problem raised in this study is the condition of Insolvency of PT. Pazia Retailindo before the bankruptcy decision , and what underlies the judge's consideration in the bankruptcy decision Number: 44 / Pdt.Sus.Pailit / 20 20 / Pn.Niaga.Jkt.Pst which refers to Law Number 37 of 2004. This research uses a Normative Juridical approach. The result of this study is that the legal considerations used by the panel of judges in deciding the bankruptcy case of PT. Pazia Retailindo complies with Law Number 37 of 2004 concerning Bankruptcy and PKPU, namely the fulfillment of all elements contained in Article 2 Paragraph 1 and Article 8 Paragraph 4 of the Bankruptcy Law and PKPU.